Mitochondrial activity as an indicator of fish freshness. (30th July 2019) - Cléach, Jérôme; Pasdois, Philippe; Marchetti, Philippe; Watier, Denis; Duflos, Guillaume; Goffier, Emmanuelle; Lacoste, Anne-Sophie; Slomianny, Christian; Grard, Thierry; Lencel, Philippe
Highlights: Mitochondria function as reliable indicator of fish freshness. Several ultrastructural post mortem damages visible in fish fillets mitochondria. Mitochondrial respiration altered in fish fillets from 96 h stored at +4 °C. Mitochondrial potential (ΔΨm ) significantly disrupted after 96 h of storage at +4 °C. Abstract: The current methods used to routinely assess freshness in the fishing industry reflect more a state of spoilage than a state of freshness. Mitochondria, the seat of cellular respiration, undergo profound changes in post mortem tissues. The objective of this study was to demonstrate that mitochondrial activity constitutes a putative early fish freshness marker. The structure of gilthead sea bream ( Sparus aurata ) muscle tissue was evaluated over time by transmission electron microscopy. Respiration was assessed in mitochondria isolated from sea bream fillets using oxygraphy. Membrane potential (ΔΨm ) was determined by fluorescence (Rhodamine 123). Mitochondrial activity of fillets stored at +4 °C was studied for 6 days. Changes in mitochondrial cristae structure appeared from Day 3 highlighting the presence of dense granules. ΔΨm and mitochondrial activity were significantly disrupted in sea bream fillets after 96 h of storage at +4 °C. Mitochondrial activity constituted a reliable and early indicator of fish freshness.